EMERGING PHARMACOLOGICAL STRATEGIES IN ALZHEIMER'S DISEASE: A REVIEW OF NOVEL THERAPEUTIC TARGETS AND DRUG INNOVATIONS - Julia Szczotka; Gabriela Szpila; Remigiusz Flakus; Żaneta Kania; Gabriela Kapłon; Weronika Perczyńska; Anna Kamieniak; Dominika Gieroba; Artur Tumiński; Marianna Chmiel; Aleksandra Sokół; Karolina Glajcar (International Journal of Innovative Technologies in Social Science, 2025)
Alzheimer’s disease (AD) is the most prevalent neurodegenerative disorder worldwide and constitutes a significant public health concern due to its rising incidence and the absence of curative therapies. This review synthesizes recent pharmacological progress in the treatment of AD, with particular emphasis on emerging therapeutic strategies and investigational drug classes. The analysis draws on clinical trial data, regulatory documents, and peer-reviewed literature published between 2017 and 2025, identified through major scientific databases including PubMed, Scopus, and ClinicalTrials.gov. The most promising advances are associated with monoclonal antibodies directed against amyloid-beta pathology, such as aducanumab, lecanemab, and donanemab, which show potential to modify disease progression but also raise concerns related to efficacy, safety, and regulatory approval. Additional innovative approaches, including tau-targeted therapies, gene editing technologies such as CRISPR-Cas9, and RNA interference (RNAi), present new therapeutic opportunities, though they remain limited by challenges such as amyloid-related imaging abnormalities (ARIA), restricted delivery across the blood–brain barrier, and uncertainties regarding long-term clinical outcomes. While currently available pharmacological options are insufficient to halt or reverse AD, recent advancements, particularly in antibody-based therapies, represent an important step toward a new therapeutic era. Nevertheless, cautious interpretation of preliminary findings and rigorous clinical validation remain essential before these strategies can be translated into widespread clinical practice.